Examining the association between serum IgG of oral bacteria and metabolic syndrome - Yang, Zhe-Yu; Fang, Wen-Hui; Kao, Chia-Chun; Chen, Wei-Liang (Frontiers in Medicine, 2022)
Aim: This investigation explored the relationship between oral bacteria and metabolic syndrome (METS). Materials and Methods: There were 4,882 subjects enrolled in this cross-sectional study from the NHANES III database. The severity of periodontitis was classified into mild, moderate and severe. We measured oral bacterial antibodies. We examined the relationship between serum immunoglobulin G (IgG) antibodies of oral bacteria and METS via performing multivariate regression analysis. Mediation analysis of oral bacteria on the correlation between periodontitis and METS was also executed. Results: After adjusting for covariates, the serum IgG antibodies of P. nigrescens, E. corrodens, and E. nodatum were associated with the presence of METS (p = 0.006, p = 0.014 and p = 0.018, respectively). Furthermore, serum IgG antibodies of P. intermedia, T. forsythia and V. parvula were positively associated with the presence of METS (p = 0.001, p = 0.011 and p = 0.002, respectively) and ≥ 4 features of METS (p = 0.019, p = 0.025 and p = 0.02, respectively). P. intermedia IgG mediated 11.2% of the relationship between periodontitis and METS. Conclusion: Serological markers of oral pathogens were correlated with the presence and the number of METS features after multivariable adjustment. Oral bacteria acted as a mediator of the correlation between periodontitis and METS. Our study provided a biologically plausible explanation for the association between periodontitis and METS, which provides a comprehensive evaluation of periodontitis.